2005
DOI: 10.1890/04-1145
|View full text |Cite
|
Sign up to set email alerts
|

Nonbreeding Habitat Occupancy and Population Processes: An Upgrade Experiment With a Migratory Bird

Abstract: Evidence is accumulating that winter habitats occupied by migratory birds produce differences in individual condition that can carry over into subsequent stages of the annual cycle. Despite strong observational evidence, experimental work is needed to strengthen support for this hypothesis. We experimentally upgraded individual American Redstarts (Setophaga ruticilla) from low‐quality second‐growth scrub habitat to high‐quality mangrove forest habitat by permanently removing behaviorally dominant, primarily ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
277
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(291 citation statements)
references
References 26 publications
11
277
3
Order By: Relevance
“…Powerful approaches exist, in particular manipulative experiments (Studds & Marra 2005, Legagneux et al 2012, Catry et al 2013, Schultner et al 2014 or long-term longitudinal measurements whereby individuals act as their own controls (Daunt et al 2014). Our approach to investigating the temporal structure in the strength of carry-over effects at multiple colonies provides an additional method of distinguishing be tween genuine carry-over effects and crossseasonal correlations (our third hypothesis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Powerful approaches exist, in particular manipulative experiments (Studds & Marra 2005, Legagneux et al 2012, Catry et al 2013, Schultner et al 2014 or long-term longitudinal measurements whereby individuals act as their own controls (Daunt et al 2014). Our approach to investigating the temporal structure in the strength of carry-over effects at multiple colonies provides an additional method of distinguishing be tween genuine carry-over effects and crossseasonal correlations (our third hypothesis).…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the relative importance of extrinsic and intrinsic effects has proved challenging in correlative studies, since they are confounded (individuals may vary both in performance and environments experienced). Two approaches have been used to date to tease apart these effects: experimental manipulation in one season as a causal test of carry-over effects (Studds & Marra 2005, Legagneux et al 2012, Catry et al 2013, Schultner et al 2014) and longitudinal measurements in individuals across a range of environmental conditions whereby they act as their own controls (Daunt et al 2014). Studies that investigate the temporal structure in the strength of seasonal interactions in multiple populations provide a third option.…”
Section: Introductionmentioning
confidence: 99%
“…Redstart habitat quality influences numerous measures of bird performance in both sexes. Individuals in high-quality habitats are typically in better physical condition [39,40] and depart earlier on spring migration [39,41] at the end of the non-breeding period than individuals in lower quality habitat. Annual survival probability is also related to overwinter habitat quality [36,42].…”
Section: Materials and Methods (A) Study Species And Sitesmentioning
confidence: 99%
“…Studds & Marra [15] showed that individuals upgraded (i.e. those that maintained their body mass compared with controls) by a removal experiment were able to depart earlier on migration and had greater return rates the following winter than controls.…”
Section: Introductionmentioning
confidence: 99%